Participation platforms in the capitals of autonomous communities - Márquez Muñoz , Laia (Cuadernos de Gobierno y Administración Pública, 2024)
This article addresses the analysis of the citizen participation platforms of those 18 capitals of the autonomous communities that have these spaces. To do this, it is identified which municipalities have platforms and what types and it is studied if there is any contextual factor that could justify it. To carry it out, the previous field work for this research consists of analyzing the digital spaces of citizen participation platforms, complemented by a bibliographic review of this subject. The results obtained demonstrate that the digital democracy system in Spain has not had the same impact in all the capitals of the autonomous communities.